Immunotherapy with intralesional Candida albicans antigen in resistant or recurrent warts: A study - Imran Majid; Saher Imran (Wolters Kluwer Medknow Publications, 2013)
Background: Warts are sometimes resistant or they tend to recur after every possible destructive therapy. Immunotherapy with skin-test antigens has been used as a viable therapeutic option in such recalcitrant cases. Aim: The aim of the study was to evaluate the response of resistant or recurrent warts to intralesional Candida albicans antigen immunotherapy. Materials and Methods: A total of 40 patients with resistant or recurrent warts who showed a positive test reaction to C. albicans antigen were given intralesional injections of purified C. albicans antigen solution in a single wart at 3-weekly intervals for a total of three doses. The patients were monitored for resolution of the injected wart as well as other untreated warts. The patients who responded positively were then followed up for any relapses over the next 6 months. Adverse events, if any, were also documented. Results: Of the 40 patients enrolled in the study, 34 completed the total treatment protocol of three injections and 6 months of follow-up. In these 34 patients, 19 (56%) showed a complete resolution of warts at all places on the body. In addition, two patients (6%) showed a partial or complete resolution of the treated wart, but there was no effect on the untreated warts. Thirteenpatients (38%) failed to show any response to the treatment regimen. In all patients showing resolution of all the warts, there were no relapses at any site over the next 6 months of follow-up. The most common adverse effect seen was pain during the intralesional injection. Conclusions: Intralesional Candida immunotherapy seems to be an effective treatment option in more than half of the patients who fail to show a positive response to destructive modes of treatment or in whom there are multiple recurrences. Limitations: The small sample size and lack of control group are the main limitations of the study.